Aerosol Route to Highly Efficient (Co)Mo/SiO2 Mesoporous Catalysts. (28th August 2013) - Colbeau‐Justin, Frédéric; Boissière, Cedric; Chaumonnot, Alexandra; Bonduelle, Audrey; Sanchez, Clément
<x xml:space="preserve">Abstract</x> One‐pot aerosol‐assisted synthesis of mesostructured (Co)Mo/SiO2 catalysts with high hydrogenation activity is reported. The evaporation*induced self‐assembly mechanism of the formation of such catalysts enables optimized interactions between each component, resulting in the tuning of localization of the active species. The high activity is probably associated with the original morphology of the active phase as well as the creation of relevant defects in its structure. Since spray‐dried mesoporous CoMo/SiO2 catalysts outperform the hydrogenation activity of classical impregnated catalysts, aerosol route appears to be a promising way for the industrial‐scale preparation of new highly efficient hydrocarbons catalysts.